ktivitas Antioksidan Dan Sifat Sensoris Teh Herbal Celup Kulit Anggur (Vitis vinifera L.) Pada Suhu Dan Waktu Pengeringan - Saragih S., Franscixkus Jamadin; Suter, I Ketut; Yusasrini, Ni Luh Ari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 3 (2021): Jurnal ITEPA, 2021)
The research aimed to determine the effect of drying temperature and time on antioxidant activity and sensory properties of herbal tea bag of grape skin and to obtain the best of temperature and drying time that can produce grape skin herbal tea bag with highest antioxidant activity and the best sensory properties.This research used a completely randomized design with factorial pattern in two factors namely, drying temperature (50 o C, 60 o C, 70 o C) and drying time (3.0 hours, 3.5 hours, 4.0 hours). There are 9 treatment combinatioms, each treatment combination was repeated 2 times so that it obtained 18 experimental units. Parameters observed were water content, total phenols, total falvonoids, antiokxidant activity, total anthocyanin, and sensory properties. The data obtained were analyzed by analysis of variance. If the treatment had a significant effect, it would be followed by the Duncan Multiple Range Test. The results showed that interaction beetwen drying temperature and time treatment had a significant (P<0.01) on antioxidant activity, total phenols, total falvonoids, total anthocyanin, extract content in water, water content, and color (scoring test), but no significant (P>0.05) on the color (hedonic test), aroma (hedonic test), taste (hedonic test), and overall acceptance. The results showed a drying temperature of 60 o C with a drying time of 3.0 hour was the optimum drying temperature and time to produce herbal tea bag of grape skin with antioxydant activity of (IC50 1512.17 ppm), water content of 5.60%, total phenol content 9.21 mg GAE/g, total flavonoids content of 6.15 mg QE/g, total anthocyanin content 8.39 mg/g, extract content 41.85%, dark purple color with hedonic color, taste, aroma and overall acceptance is neither like nor dislike.